The Hierarchy of Money - Stephanie Bell (Levy Economics Institute of Bard College, 1998)
This paper attempts to bring together several of Hyman Minsky's insights in order to suggest a relationship between the State's ability to tax and the money of the economy. Minsky recognized that money represents an IOU or promise to pay and that 'acceptability' is its important feature. He further recognized that the State can play an important role in determining whose IOUs will be accepted (both publicly and privately). I will argue that support for the Chartalist vision of money as a 'creature of the State' can be found in Minsky. Finally, I will apply the Chartalist theory to Minsky's notion of a 'hierarchy of money' in order to suggest that the State determines not only the unit in which all of the monies in the hierarchy are denominated but also influences the positioning of certain monies within the hierarchy.
Keywords: 330